A Qualitative Analysis of Experiences of Suicidal Ideation and Suicide Commitment among Females with Major Depressive Disorder in Pakistan - Qamar, Tania; Chethiyar , Saralah Devi Mariamdaran; Ibrahim, Nabisah binti (South Asian Journal of Social Sciences and Humanities, 2021)
Purpose. Suicide is a global public health problem. Because Asia accounts for 60% of all suicides worldwide, at least 60 million people are impacted by suicide or commit suicide in Asia each year. Females are more likely than males to engage in suicidal behaviour, which is defined as a complete problem of illness and death. The aim of the present research was to identify experiences of suicidal ideation and suicide commitment among females with major depressive disorder in Pakistan. Method. A sample of approximately 5 clients with major depressive disorder were approached from (Captain Mouzam Ali Shaheed Welfare Trust Hospital, Jhelum) Pakistan. The sample collected through snowball sampling strategy. Qualitative method of in-depth semi structured interview was conducted in order to get data. Beck depression inventory and suicide risk screener was used as an assessment measure. Ideographic Phenomenological Data Analysis (IPA) was utilized to examine and recorded the information in which investigator identified themes. Specific verification method was utilized to measure the credibility of the research results. Results. In outcomes, the main themes emerged in the current study and figures were drawn in order to explain the different themes. There were seven main themes were emerged in the present research were named as Etiology of Major Depressive Disorder (MDD), Effects of MDD, Psychosocial Factors, Coping with MDD, Insight about MDD, Seeking Support and Experience Difficulties During the Treatment of MDD. Novelty/Originality of The Study. Suicidal thoughts were moderately common among patients with major depressive illness. Implication. As a result, all clients with major depressive illness should be screened for suicide thoughts so that treatment can begin as soon as possible.